ANALISIS KARAKTERISTIK LAHAN SEBAGAI DASAR PENGELOLAAN KEBUN JERUK MANIS (Citrus sinensis L. Osbeck) DI SELOREJO, DAU, KABUPATEN MALANG - Norma Handa Chintya; S Soemarno (Jurnal Tanah dan Sumberdaya Lahan, 2018)
In Selorejo village, one of the centers of citrus-production in Indonesia, there are differences fruit productivity in between citrus-farmers. The high productivity citrus gardens produced 55.6 t ha-1 year-1 and in the garden with low productivity produced 26,7 t ha-1 year-1. Differences in these fruit productivity are due to differences in application of fertilizer and crop-management systems. This research was conducted by field survey and laboratory analysis. There were two observation sites as samples of the high productivity gardens (KPT) and the low productivity gardens (KPR). Soil samples taken from each garden were analyzed of soil-CEC, soil C-organic, Base saturation, soil texture, and pH to evaluate suitability of soil at each locations. Results showed that nutrient was not a dominant factor affecting fruit productivity. It is known that almost all soil characteristics suggest the same criteria.The difference was in the C-organic value that was at KPT only 0.78, whereas in KPR C-organic value reached 1,0. The actual land suitability of KPT is S3ehnr and of KPR is S3eh. Based on results of this study can be concluded that soil C-organic, land-slope and crop-management determined productivity of citrus garden.